2017
DOI: 10.1136/bmjopen-2016-014190
|View full text |Cite
|
Sign up to set email alerts
|

Does achieving the best practice tariff improve outcomes in hip fracture patients? An observational cohort study

Abstract: ObjectivesTo determine if the introduction of the best practice tariff (BPT) has improved survival of the elderly hip fracture population, or if achieving BPT results in improved survival for an individual.SettingA single university-affiliated teaching hospital.Participants2541 patients aged over 60 admitted with a neck of femur fracture between 2008 and 2010 and from 2012 to 2014 were included, to create two cohorts of patients, before and after the introduction of BPT. The post-BPT cohort was divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…A 2017 observational cohort study by Oakley et al based on 2541 patients aged over 60 admitted to a trauma centre with neck of femur fractures, found that there was a reduction in 30-day mortality from 21% in those who did not meet the BPT criteria to 6% in those who did. This was also reflected in longer-term survival figures, with a one-year mortality rate of 28.6% in those who met the tariff criteria and 42% in those who did not [ 10 ]. Since March 2012, the published NHFD 30-day mortality rates have reduced from 8.2% to 6% in April 2020 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 observational cohort study by Oakley et al based on 2541 patients aged over 60 admitted to a trauma centre with neck of femur fractures, found that there was a reduction in 30-day mortality from 21% in those who did not meet the BPT criteria to 6% in those who did. This was also reflected in longer-term survival figures, with a one-year mortality rate of 28.6% in those who met the tariff criteria and 42% in those who did not [ 10 ]. Since March 2012, the published NHFD 30-day mortality rates have reduced from 8.2% to 6% in April 2020 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to best practice reimbursement for patients with hip fractures in England, there is currently a requirement of an orthogeriatric approach including the assessment of osteoporosis to obtain the highest refund. This is also about to be established in several other countries, probably because such a "reward" delivers better outcomes [13].…”
Section: A Orthogeriatric Carementioning
confidence: 99%
“…This may well represent that the frailest patients have a delay to theatre due to a complicating medical issue which also increased their risk of mortality. There has not been a profound “improvement in outcomes at organisational level” due to the introduction of the BPT [25] . The BPT's age criteria and lack of acknowledgement of frailty could be a factor in why there has not been a significant impact on overall outcomes before and after its introduction.…”
Section: Is Clinical Frailty Scale (Cfs) a Better Predictor Of Clinicmentioning
confidence: 99%